Real-World Comparative Effectiveness of First-Line Dabrafenib Plus Trametinib Versus Immunochemotherapy in Patients with Advanced BRAF V600-Mutant Non-Small-Cell Lung Cancer: A Retrospective Cohort Study - Haizhou Yue; Qianxin Zhou; Suyu Wang; Shuangyi Li; Junyi Li; Huanzhi La; Shuyan Meng (Journal of Clinical Medicine, 2026)
Background: The optimal first-line treatment for advanced BRAF V600-mutant non-small cell lung cancer (NSCLC) remains uncertain. We compared the real-world effectiveness of first-line Dabrafenib plus trametinib (Dab+Tram) with immunochemotherapy (ICT) and other systemic regimens. Methods: This single-centre retrospective cohort study included 142 patients with unresectable stage III/IV BRAF-mutant NSCLC treated between April 2017 and May 2024. Patients were grouped by first-line regimen Dab+Tram, ICT, chemotherapy alone, or others. Primary endpoint was real-world progression-free survival (rwPFS). Propensity score matching (PSM) and multivariable Cox regression were applied to reduce measured confounding. Results: Forty-seven patients received Dab+Tram and 30 received ICT. In unadjusted analysis, Dab+Tram yielded significantly longer median rwPFS than ICT (32.5 vs. 13.3 months; p = 0.004). After PSM (25 pairs), median rwPFS was 19.6 months for Dab+Tram versus 12.6 months for ICT (HR = 1.74, 95%CI 0.85–3.66, p = 0.12). Multivariable Cox regression showed ICT, chemotherapy alone, and other regimens were independently associated with worse rwPFS versus Dab+Tram (all p < 0.05). Overall survival showed no significant difference. Dab+Tram showed some antitumor activity in later-line settings. Findings regarding pyrexia and PD-L1 subgroups were exploratory. Conclusions: In this real-world cohort, first-line Dab+Tram suggested a potential rwPFS benefit over ICT and chemotherapy. The matched comparison did not reach statistical significance, but multivariable analysis consistently supported an association between Dab+Tram and improved rwPFS. These findings provide complementary real-world evidence and require prospective validation.